(3bGYOI GdJLGhRs - (3GdbhLGfjs
(3ChdgG (B:s
(3aj bGYOI GdJLGhR hGdaQGZ , bhGYO egeI (B.. (3bGYOI GdJLGhR hGdaQGZ hCUGdI GdUMI hGdeMbbjf (B.. (3QLYgeG Edi bGYOI hGMOI GdCeQ Cf GdGNJdGa EfeG jchf eMHH (B..s
(3BNQgG (B:s
... (3hEeG HfGA Ydi chfgeG HeYfi Med GdMce (B.. (3hGdhSWjI aj GdEKHGJ HeLQO JMbjb GdMLI jchf GdMce Ydi Gdecda (B.. (3jdRe GdGSJKfGA dUMI GdYed gPG JeGe GdcdGes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3CUhd Gdabgs